The explanation of the relationship between physical factors and the quality of the concept of secondary domain with the level of social security of residents in residential settings in crime prevention based on the CPTED approach (Case study: Qazvin 400-unit residential complex) - Manizheh Akbarshahi; Jamaleddin Soheili (مسکن و محیط روستا)
Security is one of the most important human needs playing an important role in the happiness and mental health of people and society; and housing is one of the basic human needs, succeeding food and clothing. As in Maslow's hierarchy of needs, security is of secondary importance after physiological needs. However, this need has become a severe problem due to the increasing growth of housing demand as a result of the population growth and urbanization in recent decades in Iran, which has caused housing construction to reach its maximum level. Furthermore, a one-sided view has induced serious problems; because this attitude has changed the pattern of housing production that has reduced the quality of housing. Thus, their security has been reduced and the potential to commit crimes in residential areas and the fear of crime among residents has increased. Overlooking the physical and environmental criteria in terms of human needs by planners and designers of residential complexes can lead to major problems for residents. In fact, one of the problems is the lack of social security in today's complexes. In environmental design, the CPTED approach is one of the most effective approaches in promoting social security and crime prevention. The study aims to evaluate the correlation between several social security variables and the use of SPSS. The statistical population is the residents of the Qazvin 400-unit residential complex. The sample size was calculated using Cochran's formula and the multi-stage cluster sampling method was used. The reliability of the questionnaire was assessed by Cronbach's alpha and the obtained number is 0.8. Finally, based on the Friedman test, each of the proposed indicators was ranked. The performance quality indicator has the priority, and then the indicators of natural monitoring, physical quality, strengthening privacy, readability and territoriality respectively are effective in improving social security in residential complexes.